APPLICATION OF SMART FARMING IN THE USE OF FRESHWATER FISH CULTIVATION WASTEWATER FOR IOT-BASED SANSEVIERIA PLANT IRRIGATION - Iskandar, Dwi; Putri, Frestiany Regina; Anggraheni, Norhisma Zulfani (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Modern technology has brought significant changes to various sectors, including agriculture and environmental management. Challenges faced in plant cultivation include limited clean water sources and waste generated from various agricultural and aquaculture systems. The ornamental plant Sansevieria is one type of plant widely used in interior design due to its ability to improve air quality and its attractive aesthetics. By utilizing wastewater from fish ponds as an irrigation medium, it is hoped that these plants will not only be able to grow well and obtain adequate nutritional intake, but can also provide additional benefits in the form of reusing resources previously considered waste. The technology to be developed is based on the integration of the Internet of Things, which utilizes wastewater from freshwater fish aquaculture as an irrigation medium for ornamental Sansevieria plants. The method used is the Research and Development (R&D) method, a systematic approach that aims to develop, test, and refine a product through a series of gradual steps. One of the results of this research is a system that is able to demonstrate its potential in reducing dependence on clean water and providing new uses for aquaculture waste to maintain plant health efficiently.